Strategic talent development and its role in enhancing organizational competitiveness - Sanchez, Lionel Joseph T.; Pascual, Marilou P. (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to design a comprehensive soft skills training framework to address competency gaps among administrative personnel in Cabanatuan City, Philippines. A descriptive quantitative research design was used, with data gathered from 98 purposively selected administrative staff. The survey focused on key soft skills, including communication, stress management, leadership, teamwork, and conflict resolution. Results revealed high training needs in communication and stress management, with demographic factors like age and tenure influencing skill gaps. Barriers such as limited time and weak institutional support were also identified. A five-module training program was developed to address these needs through scenario-based and practical learning. Targeted soft skills training can significantly enhance employee productivity, job satisfaction, and overall organizational performance when implemented with institutional support and flexibility. Organizations should integrate flexible, structured training programs into their strategic development plans to build a resilient and adaptive workforce, particularly in fast-paced urban administrative environments.